Effect of Feeding Pellets Containing Different Concentrate to Wheat Straw Ratios on the Blood Parameters of Awassi Lambs (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2022)
This study was carried out to investigate the effect of feeding Awassi lambs different ratios of concentrate: wheat straw (C: R) on blood parameters. Five pellets of total mixed rations (TMR) containing 30:70, 40:60, 50:50, 60:40 and 70:30 of C: R ratios were prepared and offered to lambs ad libitum. The results showed that increasing the C: R ratio significantly (P